Understanding of Islamic Law Enforcement in Some Islamic Countries (Analysis of International Islamic Studies) - Wirawan, Vani (Budapest International Research and Critics University, 2021)
This religious law paper discusses the understanding of Islamic law enforcement in several countries or Islamic empires through analysis and review of hundreds of articles published in high-impact factor journals. Our data collection is carried out with a Google search engine on many scientific data-based publications such as Sagepub, Elsevier, Taylor and France, Academic Paper, and Google Books. Furthermore, the study involved the coding system, evaluation, and in-depth interpretation so that we get an understanding to answer the problems of this study. We design this study as a descriptive qualitative study on secondary data. Based on the results and discussion, we summarize the results; among others, several Islamic countries have made it mandatory for Islamic law to be applied as a whole. However, if it is not an Islamic state, the application is on agreed matters, and Muslims are obliged to fight for it gradually through a constitutional route. These findings should be input for the development of Islamic studies and law in the future.